1973
DOI: 10.1177/004051757304300406
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Durable-Press Cotton Fabrics Related to Swellability

Abstract: Fabrics with a wide range of durable-press properties were prepared by treating cotton printcloth with dimethyloldi hydroxyethyleneurea (DMDHEU) by pad-dry-cure, mild-cure, and steam-cure processes and with formaldehyde by vapor-phase, Form D, and Form W processes. Swellability in aqueous media, as measured by water retention, iso propanol retention, alkali centrifuge value, and yarn untwisting number, is discussed in relation to durable-press appear ance ratings and wrinkle recovery angles. Such measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Fabrics crosslinked in a swollen state possess wet crease resistance but little dry crease recovery [8,12,13,15,16]. Solvents in the pad bath could increase fiber swelling, which some authors have reported [11,18 ] .…”
Section: Relationship Between Physical Properties and Degree Of Crossmentioning
confidence: 99%
“…Fabrics crosslinked in a swollen state possess wet crease resistance but little dry crease recovery [8,12,13,15,16]. Solvents in the pad bath could increase fiber swelling, which some authors have reported [11,18 ] .…”
Section: Relationship Between Physical Properties and Degree Of Crossmentioning
confidence: 99%
“…Nelson and Rouselle [6] demonstrated that when crosslinking is effected in a dry state, as in the pad-dry-cure method we used in this work, the successive lamellae are closely bonded by the reagent crosslinks. While the presence of large reagent molecules in the interstices between the lamellae would increase the cross-sectional area and perimeter of the fiber, the crosslinks established would inhibit their separation when water or any swelling agent enters the fiber.…”
Section: Resultsmentioning
confidence: 87%
“…Hence, the lamellae are so separated that the reagent linkages cannot be normally formed between them. Crosslinking will then be limited to elementary fibrils within each growth layer [6]. The crosslinks themselves are, therefore, unable to change the lateral dimensions of the fiber, though the acid treatment is alone able to bring about an irreversible distention in the fiber.…”
Section: Resultsmentioning
confidence: 99%
“…Bleached printcloth. was exposed for 11 days to vapor from paraformaldehyde-H~1 by a procedure previously described [ [7]. Da0 accessibility by the method of Rousselle and Nelson [8] REPRODUCIBILITY OF THE METHOD.…”
Section: Introductionmentioning
confidence: 99%